Automatic of Correction and Program Evaluation Using Web-Based Systems - Sunu Pinasthika Fajar; Muhammad Dzulfikar Fauzi; Maria Ulfah Siregar (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2013)
Assistant or lecturer in a practicum on algorithmic learning courses it often takes a long time to correct a task collected by the practitioner. The number of tasks that must be corrected many will require a longer time. To simplify the work of the assistant or the lecturer developed a system that automatically corrects tasks that are collected by the practitioners with the black box testing method, so that the assistant only needs to publish the task and wait for the task to be corrected automatically and view or download the correction results. With the existence of this system, it is expected that the correction of tasks will be more fast, easy, and effective, and make students more able to get grades better because students are allowed to collect their assignments many times to be satisfied with the value.